2020
DOI: 10.3389/feart.2020.604807
|View full text |Cite
|
Sign up to set email alerts
|

The Footprint of Atlantic Multidecadal Oscillation on the Intensity of Tropical Cyclones Over the Western North Pacific

Abstract: Sea surface temperature (SST) over the western North Pacific (WNP) exhibits strong decadal to multidecadal variability and in this region, warm waters fuel the tropical cyclones (TCs). Observational records show pronounced decadal variations in WNP TC metrics during 1950–2018. Statistical analysis of the various TC metrics suggests that the annual average intensity of WNP TCs is closely linked to the AMO (r = 0.86 at decadal timescales, p < 0.05). Observations and coupled atmosphere-ocean simulations sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…However, post-1988, this correlation with SST weakens considerably 19 . A few studies have reported a high correlation between the Atlantic Multidecadal Oscillation (AMO) and the annual mean TC intensity in the WNP from 1950 to 2018 20 . But this strong correlation has notably diminished after 1987 (see "Methods").…”
Section: Resultsmentioning
confidence: 99%
“…However, post-1988, this correlation with SST weakens considerably 19 . A few studies have reported a high correlation between the Atlantic Multidecadal Oscillation (AMO) and the annual mean TC intensity in the WNP from 1950 to 2018 20 . But this strong correlation has notably diminished after 1987 (see "Methods").…”
Section: Resultsmentioning
confidence: 99%
“…The detected CWPE trends, even the statistically significant ones, within only several decades of records cannot be pinned down to the nature of changes as anthropogenically driven or internal variability‐dictated ones (Deser et al., 2012). In particular, the genesis and evolution of cyclones or ARs, which are considered as synoptic drivers for CWPEs, are linked to internal variability modes such as the El Niño/Southern Oscillation or Atlantic Multidecadal Oscillation (Guirguis et al., 2019; Huangfu et al., 2019; Sun et al., 2020). Hence, changes in CWPEs are possibly a result of natural variations in these modes.…”
Section: Discussionmentioning
confidence: 99%
“…More notably, the subsurface layer of the NWP was evidenced to correlate with the AMO without lag (Wu et al, 2020b). Since the 21st century, studies have indicated that the AMO dominates the multidecadal variability of the Atlantic Ocean and exhibits significant footprints on transoceanic basins, especially on the Pacific Ocean, which reflects in modulating the variability of Pacific prominent modes (such as ENSO, PDO et al) and inducing the synchronous response of physical environment (such as the anomalous warm of western Pacific SST, the increased upper ocean heat content and the intensified tropical cyclones during positive AMO phases) (Enfield et al, 2001;d'Orgeville & Peltier, 2007;Levine et al, 2017;Sun et al, 2017;Wang et al, 2017;Gong et al, 2020;Sun et al, 2020;Wu et al, 2020b;Zhang & Delworth, 2007). Moreover, a novel discovery is that the AMO played a decisive role in SKJ in the NWP during 1972-2019, which is consistent with the notion that the AMO could explain fish catch variability in the NWP by dominating the subtropical mode water (Figure 11) (Wu et al, 2020b).…”
Section: Relationships Between Skj Groups In the Nwp With Climate Pat...mentioning
confidence: 99%
“…Studies to date have explored the teleconnection mechanism between the AMO and Pacific ocean through the atmosphere bridge and ocean-atmosphere interaction, of which the direct oceanographic variations in the western pacific surface triggered by the AMO is SST (Sun et al, 2020;Wu et al, 2020b), In this sense, this paper explored the causation between local SST and SKJ, which is consistent with many studies that highlighted the importance of SST on tuna abundance (Zainuddin, 2011;Tangke et al, 2020;Salazar et al, 2021). The distinct relationships between the AMO and SKJ during two eras in this study may respond to the various stages in the thermal niche response curve of SKJ with warmer SST.…”
Section: Possible Explanations For the Nonstationary Relationship Bet...mentioning
confidence: 99%
See 1 more Smart Citation